A method and application of preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights
By grading the lignin sulfonates of different molecular weights, combining water and ethanol systems, the shape and size of silver-silver chloride composite nanocubes are regulated, and the complex and cost-effective preparation in the existing technology is solved, achieving low toxicity , low-carbon green silver nanocube preparation with stable size and shape control.
Patent Information
- Application Number
- CN202211471579.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-23
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-11-23
AI Technical Summary
The existing silver nanocube preparation methods are complex, requiring high reaction temperature and a large number of organic solvents, and the impact of polymer molecular weight on shape evolution cannot be fully explored, so it is impossible to achieve low-cost, low-carbon and green nanocubes with controllable size and shape. preparation.
By grading the lignin sulfonates of different molecular weights, combining water and ethanol systems, lignin sulfonates are used as reducing agents, surfactants and stabilizers to regulate the shape and size of silver-silver chloride composite nanocubes, and achieve the goal of Simple preparation process without the need to add other organic solvents.
The preparation of low-toxic, easy to degrade and low-priced silver-silver chloride composite nanocubes has been achieved, with stable size and shape control, reducing costs and protecting the environment.
Smart Images

Figure CN115780795B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular to a method and application of preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights. Background Art
[0002] In recent years, precious metal (silver, gold, platinum, etc.) nanoparticles have been widely used in many fields due to their good catalytic activity, electrical conductivity, unique optical properties, high specific surface area and antibacterial properties. In addition, precious metal nanocrystals with controllable size and shape have received great attention due to the strong correlation between the size and shape of nanocrystals and their electronic, optical, magnetic and catalytic properties. At present, during the growth of silver nanocrystals, surface modifiers such as polyvinylpyrrolidone (PVP), sodium citrate, hexadecyltrimethylammonium bromide (CTAB), etc. can be selectively coated on certain crystal faces of the crystal nucleus, on the one hand to prevent particle agglomeration, on the other hand to induce abnormal growth of the crystal face, thereby achieving morphological control of silver nanoparticles. In the methods for preparing silver-silver chloride composite nanocubic particles, PVP is mainly added, and the preparation process is complicated or carried out at a high reaction temperature or a large amount of organic solvent is used for washing and purification to obtain nanocubic particles. Although previous studies have demonstrated the ability of various capping agents in generating silver nanocrystals with different shapes, it is still unclear whether the initial concentration and molecular weight of the polymer will have a significant impact on the shape evolution of silver nanocrystals.
[0003] Patent publication number CN 107159275 A discloses a method for preparing silver / silver chloride composite nanocubes. The patent publication uses polyacrylamine hydrochloride as a stabilizer and diethylene glycol as a reducing agent to synthesize silver / silver chloride composite nanocubes in two steps. The disadvantage is that multiple reagents are added as functional reagents during the synthesis process, and the silver / silver chloride nanocubes cannot be reduced to silver / silver chloride nanocubes in one step, and the steps are complicated. Patent publication number CN 112221520A discloses another method for preparing silver / silver chloride composite nanocubes. The patent publication uses lignin sulfonate as a size regulator to explore the optimal usage of lignin sulfonate. The disadvantage is that lignin sulfonate is not graded, and other components may exist in the raw materials that affect the synthesis of silver nanocubes.
[0004] It can be seen that the existing materials and methods cannot fully meet the use requirements, so one or several new materials and methods are urgently needed. It is necessary to develop a low-toxic, easily degradable, low-priced, low-carbon and green biomass material to replace non-biomass materials, thereby reducing costs and protecting the environment. At the same time, without adding other organic solvents, through an extremely simple production process, the influence of different molecular weight biomass materials on the shape evolution of silver nanocrystals is studied, so as to obtain nanocubic particles with controllable size and shape. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a method and application of preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights.
[0006] The technical solution adopted by the present invention to solve the technical problem is:
[0007] A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights, comprising the following steps:
[0008] Step 1: Grading treatment of lignin sulfonate: weigh dry lignin sulfonate and 90% ethanol solution, mix them, the ratio of lignin sulfonate: ethanol solution is 15-150:300-3000 in g:mL, stir continuously at 300 rpm for 2 hours at room temperature, and then separate the lignin sulfonate solution into soluble components and insoluble residues by vacuum filtration; the insoluble residue is subjected to absolute drying treatment in an oven and then sealed, and the soluble component is subjected to rotary evaporation and freeze drying to obtain lignin sulfonate LS90; according to the above treatment method, the insoluble residue after absolute drying treatment is mixed with 70% and 40% ethanol solutions in turn to obtain lignin sulfonate LS70 and LS40, respectively; finally, the obtained LS90, LS70 and LS40 are used to prepare a series of lignin sulfonate aqueous solutions of different concentrations for standby use;
[0009] Step 2: respectively measure 0.01mM-4.5mM LS90, LS70, LS40 solution and 1mM-50mM sodium chloride solution, stir and mix for 15min-60min, and control the temperature to 25℃-70℃;
[0010] Step 3: 1 mM to 50 mM silver nitrate solution is measured and quickly injected into the mixed solution of step 2, and stirring is continued at 25° C. to 70° C. for 0.25 h to 10 h to form a silver-silver chloride composite nanocube colloidal solution; the prepared colloidal solution is centrifuged at 10,000 rpm for 20 min to 60 min, and washed with deionized water, and the process is repeated several times until the upper layer of liquid is colorless and transparent, and the silver-silver chloride composite nanocube particles are obtained after freeze drying;
[0011] The volume ratio of 0.01mM to 4.5mM LS90, LS70, and LS40 solution: 1mM to 50mM sodium chloride solution: 1mM to 50mM silver nitrate solution is 20:1.5:1.5. The obtained nanocube particles are dispersed in anhydrous ethanol, ultrasonicated for 15min to 60min, and subjected to scanning electron microscopy (SEM) test.
[0012] Furthermore, the molecular weight M of the lignin sulfonate LS90 is w The molecular weight of lignin sulfonate LS70 is 500-2000. w The molecular weight of lignin sulfonate LS40 is 800-3000. w It ranges from 1000 to 6000.
[0013] Furthermore, the lignin sulfonates LS90, LS70 and LS40 have an alcoholic hydroxyl content of 1.0 mmol / g to 8.0 mmol / g, a phenolic hydroxyl content of 0.5 mmol / g to 3.0 mmol / g, a carboxyl content of 0.1 mmol / g to 2.0 mmol / g, and a sulfonic acid content of 0.5 mmol / g to 4.0 mmol / g.
[0014] Furthermore, the S / G basic unit content of the lignin sulfonates LS90, LS70, and LS40 is 0.5 to 4.0, the content of β-O-4 aromatic ether linkage is 40 to 65 / 100Ar, the content of resin alcohol β-β linkage is 2.0 to 8.0 / 100Ar, the content of tetrahydrofuran ring β-β linkage is 1.5 to 3.0 / 100Ar, and the content of phenylcoumaran β-5 linkage is 2.0 to 6.0 / 100Ar.
[0015] Furthermore, the lignin sulfonate is derived from hardwood, softwood, and grass, and is any one of sodium lignin sulfonate, calcium lignin sulfonate, potassium lignin sulfonate, magnesium lignin sulfonate, and ammonium lignin sulfonate.
[0016] Furthermore, the optimal concentration of the lignin sulfonate LS90 for preparing silver-silver chloride composite nanocubes is 1.0mM, and the size of the silver-silver chloride composite nanocubes is 40±10nm and is stable and uniform; the optimal concentration of the lignin sulfonate LS70 for preparing silver-silver chloride composite nanocubes is 1.5mM mM, and the size of the silver-silver chloride composite nanocubes is 45±10nm and is stable and uniform; the optimal concentration of the lignin sulfonate LS40 for preparing silver-silver chloride composite nanocubes is 0.3mM, and the size of the silver-silver chloride composite nanocubes is 45±15nm and is stable and uniform.
[0017] The method described above is applied in the preparation of precious metal nanocrystals with controllable size and shape.
[0018] The beneficial effects achieved by the present invention are:
[0019] 1. The lignin sulfonate used in the method of the present invention is cheap, and has the characteristics of being easy to obtain, low in toxicity, easy to reduce, and low in price. Since the lignin sulfonate has abundant hydrophilic, hydrophobic and reducing components, it is used as a reducing agent, a surfactant, a stabilizer and a dispersant in the present invention at the same time, and no other organic solvents need to be added. In addition, no heat source needs to be added in the whole process, so that energy saving, environmental protection, low carbon and green are achieved, thereby reducing costs and protecting the environment.
[0020] 2. The method of the present invention can achieve efficient separation of various fractions of lignin sulfonate through a water and ethanol system, and obtain lignin sulfonate with concentrated molecular weight distribution and high purity by classification. The influence of narrow distribution lignin sulfonate obtained by classification and purification on the regulation of silver nanocubes is studied. The unclassified lignin sulfonate, LS90, LS70, and LS40 have different molecular weights and structures, and can regulate the optimal concentration of lignin sulfonate used in silver nanocubes to be different, and the effects are relatively stable.
[0021] 3. In different components of lignin sulfonate, the molecular weight is different. The content of S-type unit, sulfonate functional group and methoxy functional group increases with the increase of molecular weight, and the content of phenolic hydroxyl functional group decreases with the increase of molecular weight. In addition, the content of carbohydrate decreases with the increase of molecular weight. After graded treatment, the content of structural units and connecting bonds is different, and the regulation ability of lignin sulfonate on silver-silver chloride composite nanocubes has changed significantly.
[0022] 4. The preparation process of the present invention is simple and easy. Lignin sulfonate is used as a size regulator, and the lignin sulfonate has good adsorption and dispersibility. When the amount of lignin sulfonate added is appropriate, the obtained silver-silver chloride composite nanoparticles have a small size and a uniform and stable cubic structure. In addition, lignin sulfonates with different molecular weights have different abilities to regulate the preparation of silver-silver chloride composite nanocubes, so as to explore the influence of different concentrations of lignin sulfonates with different molecular weights on the shape evolution of silver nanocrystals.
[0023] 5. In the method of the present invention, lignin sulfonate is used as a reducing agent and morphology regulator. On the basis of simplifying the preparation process, lignin sulfonate with different molecular weights regulates different nanoparticle shapes, and its influence on the shape evolution of silver nanocrystals is studied. The method of preparing silver-silver chloride composite nanocubes by regulating lignin sulfonate with different molecular weights mainly forms precious metal nanocrystals with controllable size and shape.
[0024] 6. The present invention uses graded lignin sulfonate as a size and morphology regulator to explore the effects of different concentrations of lignin sulfonate with different molecular weights on the shape evolution of silver nanocrystals. When the amount of lignin sulfonate added is appropriate, the obtained silver-silver chloride composite nanocubes have a small size and a uniform and stable cubic structure. In addition, lignin sulfonate has the characteristics of being cheap and easy to obtain, low in toxicity, and easy to degrade. Therefore, the present invention provides a method with a simple and easy preparation process to obtain silver-silver chloride composite nanocubes, which is low in cost and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a scanning electron microscope (SEM) image of Ag / AgCl composite cubic nanoparticles without adding sodium lignin sulfonate solution in Comparative Example 1 of the present invention;
[0026] Figure 2 This is a scanning electron microscope (SEM) image of Ag / AgCl composite cubic nanoparticles without adding sodium chloride solution in Comparative Example 3 of the present invention;
[0027] Figure 3 This is a scanning electron microscope image of the Ag / AgCl nanocomposite cube at 25° C. with 20 mL of 1.0 mM unfractionated lignin sulfonate solution added in Comparative Example 2 of the present invention;
[0028] Figure 4 This is a scanning electron microscope image of the Ag / AgCl nanocomposite cube at 25° C. with 20 mL of 1.0 mM LS90 solution added in Example 1 of the present invention;
[0029] Figure 5 This is a scanning electron microscope image of the Ag / AgCl nanocomposite cube at 25°C with 20 mL of 1.5 mM LS70 solution added in Example 2 of the present invention;
[0030] Figure 6 This is a scanning electron microscope image of the Ag / AgCl nanocomposite cube at 25° C. with 20 mL of 0.3 mM LS40 solution added in Example 3 of the present invention;
[0031] Figure 7 The present invention is a schematic diagram of a preparation process flow chart of the method of the present invention. DETAILED DESCRIPTION
[0032] For a better understanding of the present invention, the present invention is further described in detail below in conjunction with embodiments, but the scope of protection claimed by the present invention is not limited to the scope represented by the embodiments.
[0033] The raw materials used in the present invention, unless otherwise specified, are all conventional commercially available products. The methods used in the present invention, unless otherwise specified, are all conventional methods in the art. The quality of each substance used in the present invention is the quality for conventional use.
[0034] A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights, comprising the following steps:
[0035] Step 1: Grading treatment of lignin sulfonate: weigh dry lignin sulfonate and 90% ethanol solution, mix them, the ratio of lignin sulfonate: ethanol solution is 15-150:300-3000 in g:mL, stir continuously at 300 rpm for 2 hours at room temperature, and then separate the lignin sulfonate solution into soluble components and insoluble residues by vacuum filtration; the insoluble residue is subjected to absolute drying treatment in an oven and then sealed, and the soluble component is subjected to rotary evaporation and freeze drying to obtain lignin sulfonate LS90; according to the above treatment method, the insoluble residue after absolute drying treatment is mixed with 70% and 40% ethanol solutions in turn to obtain lignin sulfonate LS70 and LS40, respectively; finally, the obtained LS90, LS70 and LS40 are used to prepare a series of lignin sulfonate aqueous solutions of different concentrations for standby use;
[0036] Step 2: respectively measure 0.01mM-4.5mM LS90, LS70, LS40 solution and 1mM-50mM sodium chloride solution, stir and mix for 15min-60min, and control the temperature to 25℃-70℃;
[0037] Step 3: 1 mM to 50 mM silver nitrate solution is measured and quickly injected into the mixed solution of step 2, and stirring is continued at 25° C. to 70° C. for 0.25 h to 10 h to form a silver-silver chloride composite nanocube colloidal solution; the prepared colloidal solution is centrifuged at 10,000 rpm for 20 min to 60 min, and washed with deionized water, and the process is repeated several times until the upper layer of liquid is colorless and transparent, and the silver-silver chloride composite nanocube particles are obtained after freeze drying;
[0038] The volume ratio of 0.01mM to 4.5mM LS90, LS70, LS40 solution: 1mM to 50mM sodium chloride solution: 1mM to 50mM silver nitrate solution is 20:1.5:1.5. The obtained nanocube particles are dispersed in anhydrous ethanol, ultrasonicated for 15min to 60min, and subjected to scanning electron microscopy (SEM) test. Figure 7 shown.
[0039] Preferably, the molecular weight M of the lignin sulfonate LS90 is w The molecular weight of lignin sulfonate LS70 is 500-2000.w The molecular weight of lignin sulfonate LS40 is 800-3000. w It ranges from 1000 to 6000.
[0040] Preferably, the lignin sulfonates LS90, LS70 and LS40 have an alcoholic hydroxyl content of 1.0 mmol / g to 8.0 mmol / g, a phenolic hydroxyl content of 0.5 mmol / g to 3.0 mmol / g, a carboxyl content of 0.1 mmol / g to 2.0 mmol / g, and a sulfonic acid content of 0.5 mmol / g to 4.0 mmol / g.
[0041] Preferably, the S / G basic unit content of the lignin sulfonates LS90, LS70, and LS40 is 0.5-4.0, the content of β-O-4 aromatic ether linkage is 40-65 / 100Ar, the content of resin alcohol β-β linkage is 2.0-8.0 / 100Ar, the content of tetrahydrofuran ring β-β linkage is 1.5-3.0 / 100Ar, and the content of phenylcoumaran β-5 linkage is 2.0-6.0 / 100Ar.
[0042] Preferably, the lignin sulfonate is derived from hardwood, softwood, or grass, and is any one of sodium lignin sulfonate, calcium lignin sulfonate, potassium lignin sulfonate, magnesium lignin sulfonate, and ammonium lignin sulfonate.
[0043] Preferably, the optimal concentration of the lignin sulfonate LS90 for preparing silver-silver chloride composite nanocubes is 1.0mM, and the size of the silver-silver chloride composite nanocubes is 40±10nm and is stable and uniform; the optimal concentration of the lignin sulfonate LS70 for preparing silver-silver chloride composite nanocubes is 1.5mM mM, and the size of the silver-silver chloride composite nanocubes is 45±10nm and is stable and uniform; the optimal concentration of the lignin sulfonate LS40 for preparing silver-silver chloride composite nanocubes is 0.3mM, and the size of the silver-silver chloride composite nanocubes is 45±15nm and is stable and uniform.
[0044] The method described above is applied in the preparation of precious metal nanocrystals with controllable size and shape.
[0045] Specifically, the relevant preparation and detection are as follows:
[0046] Experimental Example 1:
[0047] A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights, comprising the following steps:
[0048] (1) Fractionation of lignin sulfonate: 15 g of dry lignin sulfonate and 300 mL of 90% ethanol solution were weighed into a beaker, stirred at 300 rpm for 2 h at room temperature, and then the lignin sulfonate solution was separated into soluble components and insoluble residues by vacuum filtration. The insoluble residue was dried in an oven and sealed, and the soluble component was obtained by rotary evaporation and freeze drying to obtain lignin sulfonate LS90; according to the above treatment method, the insoluble residue after the dry treatment was mixed with 70% and 40% ethanol solutions in turn to obtain lignin sulfonate LS70 and LS40, respectively. Finally, the obtained LS90, LS70 and LS40 were used to prepare a series of lignin sulfonate aqueous solutions of different concentrations for use.
[0049] (2) Preparation of silver-silver chloride composite nanocubes:
[0050] Dosage of medicine:
[0051] LS90 solution: 20 mL
[0052] Sodium chloride solution: 1.5 mL
[0053] Silver nitrate solution: 1.5 mL
[0054] Anhydrous ethanol: 10mL
[0055] Measure 20mL of 1.0mM LS90 solution and 1.5mL of 10mM NaCl solution in a beaker and stir for 30 minutes, and control the temperature to 25°C. Then measure 1.5mL of 10mM silver nitrate solution and quickly inject it into the beaker, continue stirring at room temperature for 1h, centrifuge the obtained silver-silver chloride composite nanocube colloidal solution at 10000rpm for 30min, wash with deionized water, repeat several times until the upper liquid is colorless and transparent, freeze-dry to obtain silver-silver chloride composite nanocube particles, then disperse in anhydrous ethanol, ultrasonicate for 40min, and prepare the liquid sample for scanning electron microscopy (SEM). Test results are shown in Figure 4 .
[0056] Experimental Example 2:
[0057] A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights, comprising the following steps:
[0058] (1) Classification of lignin sulfonate: The lignin sulfonate classification method in Example 1 was followed.
[0059] (2) Preparation of silver-silver chloride composite nanocubes:
[0060] Dosage of medicine:
[0061] LS70 solution: 20 mL
[0062] Sodium chloride solution: 1.5 mL
[0063] Silver nitrate solution: 1.5 mL
[0064] Anhydrous ethanol: 10mL
[0065] Measure 20mL, 1.5mM LS70 solution and 1.5mL, 10mM NaCl solution in a beaker and stir for 30 minutes, and control the temperature to 25°C. Then measure 1.5mL, 10mM silver nitrate solution and quickly inject it into the beaker, continue stirring at room temperature for 1h, centrifuge the obtained silver-silver chloride composite nanocube colloidal solution at 10000rpm for 30min, wash with deionized water, repeat several times until the upper liquid is colorless and transparent, freeze-dry to obtain silver-silver chloride composite nanocube particles, then disperse in anhydrous ethanol, ultrasonicate for 40min, and prepare the liquid sample for scanning electron microscopy (SEM). Test results are shown in Figure 5 .
[0066] Experimental Example 3
[0067] A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights, comprising the following steps:
[0068] (1) Classification of lignin sulfonate: The lignin sulfonate classification method in Example 1 was followed.
[0069] (2) Preparation of silver-silver chloride composite nanocubes:
[0070] Dosage of medicine:
[0071] LS40 solution: 20 mL
[0072] Sodium chloride solution: 1.5 mL
[0073] Silver nitrate solution: 1.5 mL
[0074] Anhydrous ethanol: 10mL
[0075] Measure 20mL of 0.3mM LS40 solution and 1.5mL of 10mM NaCl solution in a beaker and stir for 30 minutes, and control the temperature to 25°C. Then measure 1.5mL of 10mM silver nitrate solution and quickly inject it into the beaker, continue stirring at room temperature for 1h, centrifuge the obtained silver-silver chloride composite nanocube colloidal solution at 10000rpm for 30min, wash with deionized water, repeat several times until the upper liquid is colorless and transparent, freeze-dry to obtain silver-silver chloride composite nanocube particles, then disperse in anhydrous ethanol, ultrasonicate for 40min, and prepare the liquid sample for scanning electron microscopy (SEM). Test results are shown in Figure 6 .
[0076] Comparative Example 1
[0077] A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights, comprising the following steps:
[0078] Preparation of silver-silver chloride composite nanocubes:
[0079] Dosage of medicine:
[0080] Sodium lignin sulfonate solution: 0mL
[0081] Sodium chloride solution: 1.5 mL
[0082] Silver nitrate solution: 1.5 mL
[0083] Anhydrous ethanol: 10mL
[0084] 1.5 mL of NaCl and 10 mM sodium chloride solution were measured and stirred in a beaker for 30 min, then 1.5 mL of 10 mM silver nitrate solution was measured and quickly injected into the beaker, and stirring was continued for 1 h at room temperature. The obtained Ag / AgCl colloidal solution was washed with deionized water and centrifuged at 10000 rpm for 30 min, and repeated several times until the upper liquid was colorless and transparent. After freeze drying, silver-silver chloride composite nanocubic particles were obtained, and then dispersed in 10 mL of anhydrous ethanol, ultrasonicated for 40 min, and then allowed to stand for 5 h. The liquid sample was used for scanning electron microscopy (SEM). The test results are shown in Figure 1 .
[0085] Comparative Example 2:
[0086] A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights, comprising the following steps:
[0087] Preparation of silver-silver chloride composite nanocubes:
[0088] Dosage of medicine:
[0089] Unfractionated sodium lignin sulfonate solution: 20 mL
[0090] Sodium chloride solution: 1.5 mL
[0091] Silver nitrate solution: 1.5 mL
[0092] Anhydrous ethanol: 10mL
[0093] Measure 20mL, 1.0mM unfractionated sodium lignin sulfonate solution and 1.5mL, 10mM NaCl solution in a beaker and stir for 30 minutes, and control the temperature to 25°C. Then measure 1.5mL, 10mM silver nitrate solution and quickly inject it into the beaker, continue stirring at room temperature for 1h, and the obtained silver-silver chloride composite nanocube colloidal solution is centrifuged at 10000rpm for 30min, washed with deionized water, and repeated several times until the upper liquid is colorless and transparent. After freeze drying, silver-silver chloride composite nanocube particles are obtained, which are then dispersed in anhydrous ethanol and ultrasonicated for 40min. The liquid sample is used for scanning electron microscopy (SEM). Test results are shown in Figure 3 .
[0094] Comparative Example 3:
[0095] A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates with different molecular weights, comprising the following steps:
[0096] Preparation of silver-silver chloride composite nanocubes:
[0097] Dosage of medicine:
[0098] LS90 solution: 20 mL
[0099] Sodium chloride solution: 0mL
[0100] Silver nitrate solution: 1.5 mL
[0101] Anhydrous ethanol: 10mL
[0102] Measure 20mL of 1.0mM LS90 solution in a beaker and stir for 30 minutes, and control the temperature to 25°C. Then measure 1.5mL of 10mM silver nitrate solution and quickly inject it into the beaker. Continue stirring for 1h at room temperature. The obtained silver-silver chloride composite nanocube colloidal solution is centrifuged at 10000rpm for 30min, washed with deionized water, and repeated several times until the upper liquid is colorless and transparent. After freeze drying, silver-silver chloride composite nanocube particles are obtained, which are then dispersed in anhydrous ethanol and ultrasonicated for 40min. The liquid sample is used for scanning electron microscopy (SEM). Test results are shown in Figure 2 .
[0103] Table 1 Key point requirements in each embodiment
[0104]
[0105] Comparative Examples 1 and 2 show that, when NaCl is added and lignin sulfonate is not added, AgCl precipitate is formed, and the precipitate particle size is 400±200nm, which is too large and very uneven; when NaCl and unclassified lignin sulfonate are added, the size of the formed silver-silver chloride composite nanocubes is 35±10nm, the particle size is uniform and stable, and the dispersibility is good.
[0106] Comparative Examples 2 and 3 show that, when only lignin sulfonate is added without adding NaCl solution, the formed silver nanoparticles are spherical with a particle size of 25±10 nm, and no regular and uniform silver nanocubes are formed.
[0107] Therefore, during the whole synthesis process, the Cl in sodium chloride - and lignin sulfonate play a key role in the nucleation and growth of silver nanocubes with single crystal structure. In the initial stage, Cl - First and Ag + The reaction generates nano-sized AgCl polyhedrons. Under the action of a reducing agent (lignin sulfonate), AgCl can be reduced to silver nuclei, then evolve into seeds, and then grow into silver nanocrystals. The intermediate AgCl is an intermediate product, i.e., a synthetic template, for further forming silver-silver chloride composite nanocubes. Under the condition of the presence of AgCl, lignin sulfonate acts on AgCl as a reducing agent and morphology regulator, thereby forming a silver nanocube structure. In the present invention, when lignin sulfonate and sodium chloride are present at the same time, there is a synergistic effect between lignin sulfonate and sodium chloride, and the two synergistically regulate regular silver nanocubes.
[0108] In Comparative Example 2, after adding 20 mL, 1.0 mM unfractionated lignin sulfonate and 1.5 mL, 10 mM NaCl, very uniform and stable silver nanocubes were regulated, with a size of 35 ± 10 nm and a small particle size. The reason for the good regulation effect is that the unfractionated lignin sulfonate has more types of functional groups, structural units and connecting bonds than the lignin sulfonates of other components, and the content is more uniform, among which the β-O-4 aromatic ether connection content is the largest. The regulated silver nanocubes have a regular morphology and a small particle size, and have good dispersibility and stability.
[0109] It can be obtained from Comparative Example 2 and Example 1 that after adding 20 mL, 1.0 mM LS90 and 1.5 mL, 10 mM NaCl, the size of the formed silver-silver chloride composite nanocubes is 40±10 nm and is relatively stable and uniform, but is larger than the size of the silver nanocubes regulated by unfractionated lignin sulfonate. This may be because the hydroxyl content, S / G content and phenylcoumaran β-5 connection content in LS90 are higher than those of the original lignin sulfonate. Hydroxyl groups can reduce silver ions to silver atoms and promote the formation of silver nanoparticles. Therefore, the content of hydroxyl functional groups plays a vital role in LS90 regulating the size and morphology of nanocrystals.
[0110] Through Example 1 and Example 2, it can be obtained that after adding 20 mL, 1.5 mM LS70 and 1.5 mL, 10 mM NaCl, the size of the formed silver-silver chloride composite nanocube is 40±15 nm, which is not much different from the particle size of the silver nanocube obtained in Example 1, but is larger than the size of the cubic silver-silver chloride composite nanocube in Comparative Example 2. This is because the content of resin alcohol β-β bonding in the LS70 structure is relatively high, so the content of resin alcohol β-β bonding during the synthesis process may determine the optimal concentration of lignin sulfonate addition to a certain extent.
[0111] It can be obtained from Comparative Example 2, Example 1, Example 2 and Example 3 that after adding 20 mL, 0.3 mM LS40 and 1.5 mL, 10 mM NaCl, the optimal concentration determined by regulating the silver nanocubes with LS40 is 0.3 mM, and the size is 45 ± 15 nm. Compared with the unfractionated lignin sulfonate, LS90 and LS70, the optimal concentration is much smaller, but uniform, regular and stable silver nanocubes can also be regulated. The carboxyl group, sulfonic acid group and phenyl coumaran β-5 linkage content in the LS40 structure are relatively high, so that the silver nanocubes have better dispersibility, indicating that the larger molecular weight, carboxyl group, sulfonic acid group and phenyl coumaran β-5 linkage content play a key role in the synthesis of silver nanocubes by LS40, among which the more phenyl coumaran content, the less β-O-4 aromatic ether linkage content, and the smaller the optimal concentration regulated by LS40.
[0112] In summary, in the present invention, when lignin sulfonate and sodium chloride are present at the same time, there is a synergistic effect between lignin sulfonate and sodium chloride, and the two synergistically regulate regular silver nanocubes. In addition, it can be seen that the lignin sulfonate without classification and purification contains more abundant and diverse functional groups and structural units, and can regulate silver nanocubes with smaller particle size and uniform dispersion. After classification, the molecular weight, purity, functional group content, and structural unit content of the lignin sulfonate are refined, and the silver-silver chloride composite nanocubes with the same effect are regulated to further reflect that in the lignin sulfonates of different components, a certain group and structure play a decisive role.
[0113] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.
Claims
1. A method for preparing silver-silver chloride composite nanocubes by regulating lignin sulfonates of different molecular weights, characterized in that: The following steps are involved: Step 1: Grading treatment of lignin sulfonate: weigh dry lignin sulfonate and 90% ethanol solution, mix them, the ratio of lignin sulfonate: ethanol solution is 15 ~150:300~3000 in g:mL, stir continuously at 300 rpm for 2 h at room temperature, and then separate the lignin sulfonate solution into soluble components and insoluble residues by vacuum filtration; the insoluble residue is subjected to absolute drying treatment in an oven and then sealed, and the soluble component is subjected to rotary evaporation and freeze drying to obtain lignin sulfonate LS90; according to the above treatment method, the insoluble residue after absolute drying treatment is mixed with 70% and 40% ethanol solutions in turn to obtain lignin sulfonate LS70 and LS40, respectively; finally, the obtained LS90, LS70 and LS40 are used to prepare a series of lignin sulfonate aqueous solutions of different concentrations for standby use; Step 2: Take 0.01 mM~4.5 mM LS90, LS70, LS40 solutions and 1 mM~50 mM sodium chloride solution respectively, stir and mix for 15 min~60 min, and control the temperature to 25 ℃~70 ℃; Step 3: Measure 1 mM~50 mM silver nitrate solution and quickly inject it into the mixed solution of step 2, and continue stirring at 25 ℃~70 ℃ for 0.25 h~10 h to form a silver-silver chloride composite nanocube colloidal solution; centrifuge the prepared colloidal solution at 10000 rpm for 20 min~60 min, wash with deionized water, repeat several times until the upper liquid is colorless and transparent, and obtain silver-silver chloride composite nanocube particles after freeze drying; Among them, the volume ratio of 0.01 mM~4.5 mM LS90, LS70, LS40 solution: 1 mM~50 mM sodium chloride solution: 1 mM~50 mM silver nitrate solution is 20:1.5:1.
5.
2. The method according to claim 1, characterized in that: The molecular weight M of the lignin sulfonate LS90 w The molecular weight of lignin sulfonate LS70 is 500~2000. w The molecular weight of lignin sulfonate LS40 is 800~3000. w It ranges from 1000 to 6000.
3. The method according to claim 1, characterized in that: The lignin sulfonates LS90, LS70 and LS40 have an alcoholic hydroxyl content of 1.0 mmol / g to 8.0 mmol / g, a phenolic hydroxyl content of 0.5 mmol / g to 3.0 mmol / g, a carboxyl content of 0.1 mmol / g to 2.0 mmol / g, and a sulfonic acid content of 0.5 mmol / g to 4.0 mmol / g.
4. The method according to claim 1, characterized in that: The S / G basic unit content of the lignin sulfonates LS90, LS70 and LS40 is 0.5-4.0, the content of β-O-4 aromatic ether linkage is 40-65 / 100Ar, the content of resin alcohol β-β linkage is 2.0-8.0 / 100Ar, the content of tetrahydrofuran ring β-β linkage is 1.5-3.0 / 100Ar, and the content of phenylcoumaran β-5 linkage is 2.0-6.0 / 100Ar.
5. The method according to claim 1, characterized in that: The lignin sulfonate is derived from hardwood, softwood, and grass, and is any one of sodium lignin sulfonate, calcium lignin sulfonate, potassium lignin sulfonate, magnesium lignin sulfonate, and ammonium lignin sulfonate.
6. The method according to any one of claims 1 to 5, characterized in that: The concentration of the lignin sulfonate LS90 for preparing the silver-silver chloride composite nanocubes was 1.0 mM, and the size of the silver-silver chloride composite nanocubes was 40±10 nm and was stable and uniform; the concentration of the lignin sulfonate LS70 for preparing the silver-silver chloride composite nanocubes was 1.5 mM, and the size of the silver-silver chloride composite nanocubes was 45±10 nm and was stable and uniform; the concentration of the lignin sulfonate LS40 for preparing the silver-silver chloride composite nanocubes was 0.3 mM, and the size of the silver-silver chloride composite nanocubes was 45±15 nm and was stable and uniform.
7. Use of the method according to any one of claims 1 to 6 in the preparation of precious metal nanocrystals with controllable size and shape.
